2011
DOI: 10.2215/cjn.10161110
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Cystatin C–Based eGFR Equations at Different GFR Levels in Children

Abstract: SummaryBackground and objectives The diagnostic accuracy of cystatin C estimated GFR (eGFR) by various cystatin C equations have varied in different studies. We hypothesized that the GFR level of enrolled patients affects the diagnostic accuracy of a cystatin C equation.Design, setting, participants, & measurements We analyzed 240 consecutively enrolled children at a single Canadian center in a prospective and cross-sectional study. Cystatin C was analyzed with nephelometry, and cystatin C eGFR was estimated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 29 publications
2
59
0
1
Order By: Relevance
“…Similar results were obtained by the pilot study conducted by Krieser et al (26) found considerable heterogeneity in the performance of CystC-based equations. In addition, by analyzing data on 240 children, Sharma et al (27) found that the diagnostic accuracy of various CystC-based equations varied with mGFR. Some equations performed better at low mGFR levels and others at high mGFR levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by the pilot study conducted by Krieser et al (26) found considerable heterogeneity in the performance of CystC-based equations. In addition, by analyzing data on 240 children, Sharma et al (27) found that the diagnostic accuracy of various CystC-based equations varied with mGFR. Some equations performed better at low mGFR levels and others at high mGFR levels.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed analysis of Tables 17 and 18 The Filler equation has been found to significantly overestimate the value of real GFR by the mean percentage of 7.8-39%, what has been pointed out. 29,37,38 The bi-marker equation of Zappitelli shows a slight mean error of 18.5% and its accuracy mildly decreases only at high values of GFR >135 mL/min/1.73 m 2 . Importantly at GFR >135 mL/min/1.73 m 2 , none of the equations, with the exception of the modified trimarker Schwartz formula (GFR S3M C), shows a significant correlation with the reference method.…”
Section: Discussionmentioning
confidence: 99%
“…29,34 This is why the relative error (RE) expressed as a percentage value was chosen as the basic method of comparing to GFR I and to values originating from the analyzed equation:…”
Section: Proposal Of Equations Modification and Employed Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the best-fit model of correlation between iGFR and CysC is linear, but it is still far below the KDOQI targets to be validated, with ,90% of estimated GFRs reaching 30% accuracy (21). Regarding the solely SCreat-based formulas for eGFR, the linear model proposed by Schwartz et al is inaccurate SCreat, serum creatinine; CysC, cystatin C. (24). All these findings have important implications for public health and clinical practice, particularly in conditions of less renal impairment or normal GFR.…”
Section: Discussionmentioning
confidence: 99%